Stromal Fibroblast in Age-Related Cancer: Role in Tumorigenesis and Potential as Novel Therapeutic Target - Elkhattouti, Abdelouahid; Hassan, Mohamed; Gomez, Christian R. (Frontiers in Oncology, 2015)
Incidence of most common cancers increases with age due to accumulation of damage to cells and tissues. Stroma, the structure close to the basement membrane, is gaining increased attention from clinicians and researchers due to its increasingly, yet incompletely understood role in the development of age-related cancer. With advanced age, stroma generates a pro-tumorigenic microenvironment, exemplified by the secretory-associated specific phenotype (SASP). Components of the SASP such as cytokines, chemokines, and high energy metabolites are main drivers of age-related cancer initiation and sustain its progression. Our purpose is to provide insight into the mechanistic role of the stroma, with particular emphasis on stromal fibroblasts, on the development of age-related tumors. We also present evidence of the potential of the stroma as target for tumor therapy. Likewise, a rationale for age-related antitumor therapy targeting the stroma is presented. We expect to foster debate on the underlining basis of age-related cancer pathobiology. We also would like to promote discussion on novel stroma-based anticancer therapeutic strategies tailored to treat the elderly.